Can We Assess Pulsus Paradoxus through Polysomnography in a Patient with Chronic Obstructive Pulmonary Disease and Sleep-Disordered Breathing? - Liendo, Cesar (J Clin Sleep Med, 2016)
Pulsus paradoxus (PP) is a decrease in systolic blood pressure greater than 10 mm Hg during inspiration that occurs in various medical conditions. Using polysomnography pulse oximetry signal, photoplethysmography variations of the amplitude of the pulse pressure within the respiratory cycle were observed. There is a proportional relationship between the changes of inspiratory waveform values and the generated PP. A 59-year-old male underwent polysomnography that showed sleep hypoxemia, obstructive sleep-disordered breathing (apnea hypopnea index [AHI] = 5.1and respiratory disturbance index [RDI] = 87.9), with variations of pulse pressure induced primarily by inspiration. The highest variations in the pulse wave were observed in NREM sleep during obstructive respiratory events and in biocalibration during nasal breathing. The lowest variations occurred after the correction of inspiratory obstructive events and during biocalibration when asked to hold his breath. CITATION: Liendo C, Dalal A, Hinds E, Sara S, Chernyshev O, Nutakki S, de Castro JR, Chesson A. Can we assess pulsus paradoxus through polysomnography in a patient with chronic obstructive pulmonary disease and sleep-disordered breathing? J Clin Sleep Med 2016;12(6):917–919.